Nikolaos A. Chrissidis, An Academy at the Court of the Tsars. Greek Scholars and Jesu-it Education in Early Modern Russia, Northern Illinois University Press, 2016 - ΚΑΡΡΑΣ, ΓΙΑΝΝΗΣ (Μνήμων, 2024)
Δεν διατίθεται περίληψη